Stella Batts : hair today, gone tomorrow - Sheinmel, Courtney (Sheinmel, Courtney. Stella Batts, 2012)
When Stella learns that her best friend Willa is moving away, she makes a wish and tries with a magic potion to keep her in Redwood City, California.